Further Development of the Short Psychopathy Rating Scale - Međedović, Janko; Romić, Emilija; Batinić, Nevena; Filipović, Ognjen; Bašić, Đorđe; Pavlović, Svetlana; Mijatović, Nevena; Cupać, Đorđe (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
In the present work, we describe the further development of the Short Psychopathy Rating Scale (SPRS), a 9-item inventory for measuring three psychopathy traits: Deceitfulness, Emotional coldness and Recklessness. We administered this inventory on a sample of 210 students (76% females, Mage = 21.21; SD = 2.10) who rated their parents on psychopathic traits. Analyses were conducted on 373 participants (54% females, Mage = 51.47; SD = 5.91). We calculated Cronbach's α coefficient as a reliability estimate, tested the latent structure of the construct using Confirmatory Factor Analysis (CFA) and explored the validity of the SPRS scales by examining their relations with the Triarchic Psychopathy Measure. Psychopathy scales showed acceptable reliabilities, having in mind that all scales consisted of 3 items (αs in the range from .60 to .68). CFA showed good fit for the SPRS model: χ²(24) = 85.57; p < .01; NFI = .88; CFI = .91; RMSEA = .078. Predictable sex differences were found – males had significantly higher scores on all three psychopathy traits. Finally, the validity of the SPRS scales was determined by establishing relationships with the psychopathy traits of the Triarchic Psychopathy Measure: Meanness, Boldness, and Disinhibition. Deceitfulness showed unique relations with Boldness, Emotional coldness with Meanness, and Recklessness with Disinhibition, as expected. In sum, the SPRS measures showed acceptable reliabilities, an adequate factor structure, and excellent convergent and divergent validity. However, there is still room for improvement, especially in elevating scale reliabilities.